Membangun Ekosistem Kewirausahaan Digital Syariah Bagi UMKM di Wilayah Jawa Timur dan Nusa Tenggara Barat - M. Adhi Prasnowo; Muhajir Sulthonul Aziz; Meithiana Indrasari; Eko Pamuji; Dwi Prasetyo (Prapanca : Jurnal Abdimas, 2023)
In the era of digitalization that currently affects the development of information technology that continues to grow, the development of digital-based technology is getting faster and more sophisticated. Digitalization of business patterns and the sharia economy is still a big challenge and opportunity to be implemented in Indonesia. The sharia economy and business pattern with all its infrastructure and instruments must be able to take this enormous opportunity. This golden opportunity must be utilized as well as possible by sharia economic activists. So it is necessary to implement a Digital Entrepreneurship Academy (DEA) Sharia Digital Entrepreneurship training program with target communities in East Java and West Nusa Tenggara. The training program is carried out with a curriculum structure that is relevant to the target community with an offline training method for 2 days with 13 Hours of Meeting. The implementation of the Digital Entrepreneurship Academy (DEA) Shariah Digital Entrepreneurship Training for small and medium businesses that has been carried out with a meeting curriculum arrangement is able to provide insight into the target community to start the sharia pattern and form a sharia entrepreneurial ecosystem so that the economic system is stronger. It was explained that 954 participants considered that the material was relevant to the problems faced by the participants and that the benefits of the training could be judged to have a decent level of sustainability to continue to be implemented.